2016
DOI: 10.5944/rppc.vol.21.num.2.2016.16146
|View full text |Cite
|
Sign up to set email alerts
|

Burnout y factores estresantes en profesionales sanitarios de las unidades de cuidados intensivos

Abstract: Resumen: El objetivo del presente estudio fue estudiar el burnout y los factores que provocan estrés en los profesionales que trabajan en las unidades de cuidados intensivos (UCI). Participaron en el estudio 117 sanitarios que respondieron a un registro sociodemográfico, al cuestionario Maslach Burnout Inventory (MBI) y al Cuestionario de Factores Estresantes en UCI. Los factores más estresantes eran la sobrecarga de trabajo y la falta de personal. Más del 30% de la muestra presentaba puntuaciones elevadas en … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 12 publications
0
10
0
6
Order By: Relevance
“…A study ( 46 ) found that women reported higher levels of burnout, although with no significant differences, while men experienced higher levels of Depersonalization, with Emotional Exhaustion predicted by professional experience and gender (higher in the most experienced participants and women). Regarding Depersonalization, the variance was only explained by gender and women were less likely to evidence symptoms of Depersonalization than men.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A study ( 46 ) found that women reported higher levels of burnout, although with no significant differences, while men experienced higher levels of Depersonalization, with Emotional Exhaustion predicted by professional experience and gender (higher in the most experienced participants and women). Regarding Depersonalization, the variance was only explained by gender and women were less likely to evidence symptoms of Depersonalization than men.…”
Section: Discussionmentioning
confidence: 98%
“…In Spain, in a hospital, analysed the prevalence and typology of burnout syndrome in nursing professionals ( 33 ) , while other study ( 3 ) conducted a systematic review to identify the prevalence of Emotional Exhaustion, Depersonalization and Personal Achievement of primary health care nurses. Also authors ( 34 ) investigated burnout and stress causes among professionals working in intensive care units (physicians, nurses and assistants, showing respectively 28%, 49% and 22%). In Brazil, different studies have been developed particularly assessing the professional performance and factors associated with burnout among health professionals ( 5 ) , the prevalence of burnout predictors in nurses of an intensive care unit ( 35 ) , the relationship between burnout and depressive symptoms in nurses of an intensive care unit ( 36 ) , the association between burnout and job shifts of the nursing staff of a hospital ( 37 ) , and burnout and working environments among nurses working in public health institutions ( 38 ) .…”
Section: Introductionmentioning
confidence: 99%
“…With regard to gender, some authors underline its higher prevalence in women than in men (Ballester-Arnal et al, 2016), while others show higher levels of burnout in men than in women (Pera and Serra-Prat, 2002), and finally, Peralta-Ayala and Moya (2017) did not find any gender differences in burnout.…”
Section: Introductionmentioning
confidence: 99%
“…La evidencia de la literatura suele indicar que existe cierta asociación entre el síndrome de burnout y el grado percibido de bienestar o salud (Aluja, 1997;Ballester-Arnal et al, 2016;Esteras, Chorot y Sandín, 2018;García, 1991;García, Sáez y Llor, 2000;Santamaría y Soto, 2005), así como también con los niveles de ansiedad y depresión (Firth, McKeown, Mcintee y Britton, 1987;Esteras et al, 2018;García et al, 2000. Aunque los estudios relacionados con el ámbito de la docencia son escasos, algunos trabajos han encontrado una rela-ción significativa entre el síndrome de burnout y los problemas de salud en profesionales de la enseñanza (Capone, Joshanloo y Park, 2019;Durán, Extremera, Montalbán y Rey, 2005;Holt, Fine y Tollefton, 1987;Greenglass y Burke, 1988).…”
Section: Introductionunclassified